Freshwater and salt-water influence in human identification by analysis of DNA: an epidemiologic and laboratory study - Jamilly de Oliveira Musse; Amanda da Costa Nardis; Evelyn K. Anzai; Mário H. Hirata; Regina Maria Barreto x Cicarelli; Rogério Nogueira de Oliveira (Universidade Estadual de Campinas, 2015)
Aim: To investigate the casuistry of drowning cases by reviewing the records from the Forensic Medicine Institute Nina Rodrigues in the city of Salvador, BA, Brazil, and to verify the potential of DNA recovery in human teeth immersed in water. Methods: An epidemiological survey was conducted followed by a laboratorial phase, in which 40 teeth were immersed in fresh and salt-water, the DNA was extracted by the organic method and amplified by polymerase chain reaction, using the amelogenin as initiator. The electrophoresis initially occurred in agarose gel and later in polyacrylamide gel. Results: In the present survey, 346 deaths from drowning were observed, most of them in salt-water (51.73%), with a predominance of male victims (86.13%) aged from 18 to 35 years-old (37.94%). Dentists identified 14.74% of the victims. DNA was recovered in 37.5% from the samples, most from teeth immersed in freshwater. Polyacrylamide gel analysis in samples that were amplified in agarose gel allowed correct gender identification in 83.3% of the cases. However, allele loss was observed in samples of two victims, jeopardizing gender determination. Conclusions: Dental exposure to water interfered in DNA recovery. The gender investigation using the amelogenin as initiator was effective.